Daily movement, sleeping sites and canopy level use of habituated silvered-leaf monkeys (Trachypithecus cristatus)in Bukit Malawati, Kuala Selangor, Malaysia - Kamarul Hambali; Badrul Munir Md-Zain; Aainaa Amir (Universiti Malaysia Terengganu, 2016)
A study on the daily movement, common use of sleeping sites, and canopy level of habituated silvered-leaf monkeys (Trachypithecus cristatus selangorensis) was carried out in Bukit Malawati, Kuala Selangor, Malaysia. The scan sampling method was used to observe behavioral data. The results showed that the daily movement of the study group was small and limited in the usage of their territories. They tended to move in the range of 10 to 200 m per day. The home range for the study group was estimated to be at 0.01 km2. The short and limited movement of the study group was closely related to the territorial factor. The factor of abundance and distribution of food resources was also a major factor affecting the movement of silvered-leaf monkeys in the study area. In addition, the movement pattern of the study group was believed to have been influenced by the habituation process. The movement styles that were used by the study group were crawling, hanging, and jumping at the study area. The forest structure and its contents are extremely important in determining the height of tree that will become the place for where silvered-leaf monkeys will search for food. The study showed that the study group spent the most time in the lower canopy (27%), followed by the middle canopy (26.3%), ground level (25.8%), upper canopy (16%), and finally the emergence (5%). For the choice of sleeping sites, members of the study group selected chosen higher canopies from the ground, specifically; the middle canopy (33%), upper canopy (30%), emergence (20%), and lower canopy (17%). It was found that the study group did not choose sleeping site at the ground level, where they would not be able to prevent attacks from the predators. Treetops act as protection for silvered-leaf monkeys.